Hubungan Pengetahuan Kewarganegaraan dengan Partisipasi Politik Mahasiswa - Tri Wulandari, Nisa A'rafiyah; Dayati, Umi (Universitas Negeri Malang, 2019)
This study aims to test the correlation of civic knowledge towards political participation at Law and Civic students in Malang State University. Quantitative research with this survey design uses stratifiedproportionalrandomsampling.Theresultsshowthatthelevel of civic knowledge is intermediate, and the level of political participation is high. Hypothesis testing proves that there is a strong correlation of civic knowledge towards political participation at Law and Civic students. This strong correlation indicates that the level of civic knowledge can be one of the factors that can influence the high level of student participation.